An analysis of the performance of the companies in Constanta County which operate in the real estate transactions field in the context of sustainable development - Aivaz, Kamer-Ainur; Avram, Constantin (Technium Social Sciences Journal, 2021)
As time went on, Constanta County has become one of the emerging poles of residential development in Romania, primarily due to its excellent positioning as an economic hub driven by international trade, doubled by a tourism potential with a high degree of long-term growth. In this context, performance measurement remains a constant concern of the entire economic sector that can ensure the progress of an entity. The purpose of this paper is to carry out a dynamic analysis over an 11-year period of the profit margin at the level of the economic agents in Constanta County whose main object of activity is, according to the NACE classification, Real Estate activities/transactions. In the analyzed period, the year 2015 stands out, in which the resumption of lending for large projects and the return of investor confidence in the real estate sector created a contagious euphoria on the market which, coupled with the income accumulated in the crisis by investors looking for profitable capital investments, led to the emergence of a wave of acquisitions, thus stimulating the real estate transactions market. Moreover, although the Coronavirus pandemic has affected the entire planet, more precisely all the economic sectors and the real estate market has not been an exception, the evolution of real estate transactions in the year 2020 was beyond the expectations of specialists in Romania, Romanians showing an appetite for this kind of transactions also in the year of the pandemic.